Dynamics of Onchocerca volvulus microfilarial densities after ivermectin treatment in an ivermectin-naïve and a multiply treated population from Cameroon. - Sébastien D S Pion; Hugues C Nana-Djeunga; Joseph Kamgno; Nicholas Tendongfor; Samuel Wanji; Flobert Njiokou; Roger K Prichard; Michel Boussinesq (Public Library of Science (PLoS), 2013)
BACKGROUND/OBJECTIVE: Ivermectin has been the keystone of onchocerciasis control for the last 25 years. Sub-optimal responses to the drug have been reported in Ghanaian communities under long-term treatment. We assessed, in two Cameroonian foci, whether the microfilaricidal and/or embryostatic effects of ivermectin on Onchocerca volvulus have been altered after several years of drug pressure. METHODS: We compared the dynamics of O. volvulus skin microfilarial densities after ivermectin treatment in two cohorts with contrasting exposure to this drug: one received repeated treatment for 13 years whereas the other had no history of large-scale treatments (referred to as controls). Microfilarial densities were assessed 15, 80 and 180 days after ivermectin in 122 multiply treated and 127 ivermectin-naïve individuals. Comparisons were adjusted for individual factors related to microfilarial density: age and number of nodules. FINDINGS: Two weeks post ivermectin, microfilarial density dropped equally (98% reduction) in the ivermectin-naïve and multiply treated groups. Between 15 and 180 days post ivermectin, the proportion of individuals with skin microfilariae doubled (from 30.8% to 67.8%) in controls and quadrupled (from 19.8% to 76.9%) in multiply treated individuals but the mean densities remained low in both sites. In fact, between 15 and 80 days, the repopulation rate was significantly higher in the multiply treated individuals than in the controls but no such difference was demonstrated when extending the follow-up to 180 days. The repopulation rate by microfilariae was associated with host factors: negatively with age and positively with the number of nodules. CONCLUSION: These observations may indicate that the worms from the multi-treated area recover mf productivity earlier but would be less productive than the worms from the ivermectin-naïve area between 80 and 180 days after ivermectin. Moreover, they do not support the operation of a strong cumulative effect of repeated treatments on the fecundity of female worms as previously described.